Frankenstein - Abdo, Kenny (ABDO Publishing Company, 2018)
This title focuses on Frankenstein and gives information related to their origin, Hollywood influence, and legacy they left behind. The title is complete with beautiful and colorful photographs, simple text, and a database for added activities. Aligned to Common Core Standards and correlated to state standards, Bolt! is an imprint of Abdo Zoom, a division of ABDO.
Description based on publisher supplied metadata and other sources
Keywords: Frankenstein; Victor (Fictitious character); Monsters in literature; Monsters in mass media; Electronic books